The role of Vitamin D in the prevention and treatment of inflammatory skin diseases – atopic dermatitis and psoriasis - literature review - Baciur, Patrycja; Chmura, Anna; Skowrońska, Katarzyna; Białas, Filip; Pondel , Kamil (Journal of Education, Health and Sport, 2022)
Vitamin D is an important substance that has a pleiotropic range of action in the human body. Its important role is to influence the cells of the immune system and regulate the body's inflammatory response. Many physiological processes at the immune level have been discovered to prove this. Vitamin D deficiency is common and results mainly from limited sun exposure at certain latitudes or from insufficient dietary supply. This likely increases the risk of many diseases, including autoimmune diseases. Numerous evidence shows that also in skin diseases such as AD or psoriasis, the level of calcitriol is of great importance, and its supplementation in the prevention and treatment of these diseases promotes frequent remissions and improves the clinical condition of patients. Therapy with high doses of vitamin D analogues can be effective and safe. The exact knowledge of the properties of this vitamin probably allows for its real and effective use in the treatment of skin diseases. However, numerous large-scale studies are still needed to more accurately determine the dosage, effects of this therapy and to use this preparation with certainty and the highest possible effectiveness in everyday medical practice.